Cash Holdings, Investment Efficiency, and the Russia–Ukraine War: Evidence from Indonesian Energy Firms - Mikha Valentino; Retno Yuni Nur Susilowati (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Sekolah Tinggi Ilmu Ekonomi Krakatau, 2026)
Purpose: This study examines the effect of cash holdings on corporate investment efficiency in energy sector companies listed on the Indonesia Stock Exchange (IDX) from 2016 to 2023, with the Russian invasion of Ukraine as a moderating variable. Methodology: Using a quantitative approach, secondary data from 62 energy firms (389 observations) were analyzed using Stata through descriptive statistics, panel model selection, classical assumptions, and hypothesis testing. Results: The results indicate that cash holdings positively and significantly affect investment efficiency, while the Russian invasion of Ukraine does not moderate this relationship and only acts as a predictor moderator that shows a direct effect on investment efficiency. Conclusions: The level of cash holdings plays an important role in influencing investment efficiency, whereas the Russian invasion of Ukraine does not affect this relationship in the Indonesian energy sector. Limitations: This study is limited to Huang’s (2020) model, which may vary in accuracy from alternatives, and a temporal dummy proxy for the Russian Invasion of Ukraine that fails to capture geopolitical shock intensity. Contribution: This study contributes to the literature and corporate decision-making by providing empirical evidence on how cash holdings affect investment efficiency and highlighting the moderating role of the Russian invasion of Ukraine in this relationship.